Spillovers from Global and Regional Shocks to Armenia - Ayvazyan, Knarik (IMF Working Papers; Working Paper ;, 2015)
Using a structural vector auto-regression (SVAR) model, this paper examines the size, geographical sources, and transmission channels of global and regional shocks to the Armenian economy. Results show that Armenian economic activity is strongly influenced by global demand shocks and changes in oil prices, yet relatively immune to financial volatility. Transmission takes place through the Russian and EU economies, remittances, and external borrowing. The role of exports and tourism is low. Russia is key in transforming the potentially negative impact of an increase in oil prices into a positive event, through stronger remittances and exports. Services and construction, which depend significantly on remittances and external borrowing, are the most affected by global and regional shocks.